Towards Effective Written Feedback: Insights from Lecturers and Students in Thesis Supervision - Rosyidi, Unifah; Rahmatiah, Rahmatiah (IJBLE Scientific Publications Community Inc., 2024)
This research investigates how both lecturers and students perceive written feedback during thesis writing, as well as the stress such feedback may cause students. Employing a qualitative content analysis approach, the study examined thesis drafts enriched with written feedback, along with questionnaires and interviews conducted with four lecturers and eight students. Findings reveal that lecturers and students share similar perceptions regarding feedback delivery, focus on content, grammar correction, clarity, and timing. However, differences emerged concerning the use of marks, the imbalance of positive and negative feedback, errors in feedback, and insufficient psychological consideration, three of which were identified as sources of stress for students. The study recommends further exploration of effective written communication strategies to reduce stress in the thesis-writing process.